Finite element analysis of steel frame structure for food court using ANSYS - Mohd Khairul Azam, Md Khairudin (2015)
In this research, a 3D steel frame structure has been analyze using ANSYS software and manual calculation. This research is to determine the strain, stress, maximum deflection, deformation and also checking the structure according to Eurocode 3. As we know the uses of steel frame structure in the construction is widely used. It easy to conduct and construct and at the same time reduced the duration time. The type of material and the geometry for the structure was satisfied in cases it passed all the designing for tensile, buckling and compression. From the result of simulation we can know the behavior of the structure under the input parameter that applied. Then, from the probabilistic analysis, we collect the result of cumulative distribution function, the histogram plot for input and output parameter, sensitivity plot and simple history plot for all parameter.